2019
DOI: 10.1088/1755-1315/323/1/012078
|View full text |Cite
|
Sign up to set email alerts
|

Integration of multiple methodologies to evaluate effects of Nature Based Solutions on urban climate mitigation and adaptation

Abstract: Nature Based Solutions contribute both to mitigate and to adapt the cities to the impacts caused by climate change at urban level. Several methods and tools exist for assessing each strategy. However, none of them allow to cover the whole steps included from analyzing climate trends that could affect the cities, to NBS effectiveness. This paper reviews and classifies existing methods according to the relevant steps of climate resilience and NBS effectiveness, and a combination of various of those methods is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The study also revealed that, among the seven societal challenges formulated by the IUCN, the analysed pre-existing interventions respond, in a broader scope, to human health and climate change adaptation and mitigation challenges. This is consistent with the research of Castellar et al [39] or López et al [26], which revealed that these challenges are responded to by several NBS types, such as gardens, parks and green corridors. Health and wellbeing have also been recognized as two of the urban (sub)challenges most frequently assessed in the literature [43] and as being in high demand by urban society [15,33].…”
Section: Pre-existing Interventions As Nbs Candidates: a Case Study E...supporting
confidence: 92%
See 2 more Smart Citations
“…The study also revealed that, among the seven societal challenges formulated by the IUCN, the analysed pre-existing interventions respond, in a broader scope, to human health and climate change adaptation and mitigation challenges. This is consistent with the research of Castellar et al [39] or López et al [26], which revealed that these challenges are responded to by several NBS types, such as gardens, parks and green corridors. Health and wellbeing have also been recognized as two of the urban (sub)challenges most frequently assessed in the literature [43] and as being in high demand by urban society [15,33].…”
Section: Pre-existing Interventions As Nbs Candidates: a Case Study E...supporting
confidence: 92%
“…The assessment was conducted in relation to the seven societal challenges (SCh) listed by the IUCN [9], which are briefly described in Table 2, referring to their link to the Sustainable Development Goals (SDG). The challenge-orientation criteria (Table 2, Column A) were based on an on-systematic review of both peer-reviewed research papers [4,7,8,11,12,16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and relevant reports published by the EC [1, 13,37], IUCN [2,11] and UNEP [38]. Each criterion was selected on the basis of the following principles: (1) relevance to the topic under study, which is how to meet a given societal challenge; (2) universal character, so that NBS featuring different levels of human intervention in the ecosystem of different spatial extents and located in various areas can be assessed; and (3) measurability, meaning the availability of data or ease of data collection.…”
Section: Challenge-orientation Assessmentmentioning
confidence: 99%
See 1 more Smart Citation